Dampak Keberadaan Universitas Jenderal Soedirman terhadap Pendapatan Masyarakat di Kecamatan Purwokerto Utara - Choirunisa, Nabila; Widyastuti, Della; Mardotillah, Puja; Anggraeni, Oki; Rahajuni, Dijan (Edukasi IPS, 2025)
This study aims to examine “The Impact of the Presence of Universitas Jenderal Soedirman on Community Income in North Purwokerto District.” The research method employed was a qualitative approach. The population consisted of residents in North Purwokerto District, while the sample included boarding house owners in Grendeng Village. Data were collected through observation and interviews, using observation forms and questionnaires as research instruments. The results indicate that the presence of Universitas Jenderal Soedirman has brought positive impacts, such as increased business and employment opportunities, the concentration of economic activities, and the growth of various businesses including boarding houses, photocopy services, food stalls, coffee shops, grocery stores, laundry services, and other enterprises. On the other hand, negative impacts have emerged due to population growth and high levels of community activity. Population density can trigger various problems. Additionally, high mobility may lead to social issues and environmental consequences. The large number of students coming from outside Purwokerto, with diverse cultural backgrounds, makes it challenging for the local community to preserve their original culture.